Building bridges connecting faculty, students, and the college library - McAdoo, Monty L. (IG library, 2010)
Packed with useful tips and techniques, this handy guide offers advice on working with both students and instructors to develop successful assignments that integrate your library's resources. Managing relationships among faculty and students can be complicated, "Building Bridges" shows how you can establish effective liaisons, with: tips to alert instructors of the library's ever-changing resources in order to craft stimulating, up-to-date assignments; straightforward, practical discussion of relationships among students, faculty, and information professionals, and how these groups can work better together; and, resources, references, and more for librarians who wish to better understand library assignments. The information in this book will help you bridge the gap between the library, faculty, and students to make sure your library's resources are being utilized to their fullest potential.